Ophthalmic congenital anomalies: spectrum and systemic associations in a Nigerian tertiary hospital (2017)
Background: To document the pattern of ophthalmic congenital anomalies and their associated systemic anomalies in Nigeria’s foremost university teaching hospital. Methods: Retrospective cross-sectional study conducted at the University College Hospital, Ibadan from January 2009 to December 2013. Clinic and ward registers of various departments and units in the hospital were reviewed to identify children with any structural abnormality, present at birth, which involved the eye and/or its adnexae. Results: Two hundred and forty eight children with 259 ophthalmic congenital anomalies were studied. The median age was 1.2 years with an interquartile range of 4.6 years. The male to female ratio was 1.27:1. Congenital cataract was found in 109 (44%) patients; 40 (15.4%) children had congenital glaucoma, and whole globe anomalies were observed in 18 (6.9%) children. Eighteen (7.9%) children had a family history of congenital anomalies. Associated systemic congenital anomalies were seen in 32 (12.9%) patients with the most common being cardiovascular anomalies in 13 (5.2%) patients. Children who had congenital cataracts were more likely to have multiple associated systemic anomalies (p<0.005). All the children who had associated cardiovascular anomalies had congenital cataracts (p= 0.001). Conclusion: The commonest ophthalmic congenital anomaly presenting for tertiary care in Ibadan is congenital cataract. Cardiovascular anomalies are the commonest systemic association of ophthalmic congenital anomalies. There is an urgent need for the establishment of a registry for congenital anomalies with effective screening and active surveillance within the Nigerian health system.